1999
DOI: 10.1038/sj.bjc.6690396
|View full text |Cite
|
Sign up to set email alerts
|

Foods, nutrients and prostate cancer: a case–control study in Uruguay

Abstract: Prostate cancer is the second commonest malignancy among Uruguayan men, with an age-adjusted incidence rate of 32.6 per 100 000 (Parkin et al, 1997). According to a previous study (De Stefani et al, 1994), the mortality rate for prostate cancer has increased by 77% in the period between 1953 and 1991. Also, migrants from Spain and Italy have increased their risk of prostate cancer after arrival in Uruguay, suggesting the importance of environmental factors (De Stefani et al, 1990).In the only previous analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
73
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 23 publications
10
73
1
5
Order By: Relevance
“…Generally, fruit intake has not been associated with prostate cancer risk. 3 Small benefits from increased total vegetable consumption have been reported by several studies, 2,5,7,24,31 but not supported by others. 8,9 In particular, no associations were found in the large EPIC cohort.…”
Section: -26mentioning
confidence: 90%
“…Generally, fruit intake has not been associated with prostate cancer risk. 3 Small benefits from increased total vegetable consumption have been reported by several studies, 2,5,7,24,31 but not supported by others. 8,9 In particular, no associations were found in the large EPIC cohort.…”
Section: -26mentioning
confidence: 90%
“…take is positively associated with prostate cancer, [41][42][43][44][45][46][47] though some case-control studies have suggested no association between energy intake and prostate cancer. [48][49][50][51][52] In this study, energy intake increased the risk of prostate cancer to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…27). For nine evaluated case-control studies (9,(202)(203)(204)(205)(206)(207)(208)(209), the mean relative risk was 1.08 and the range was 0.40-1.70 (Fig. 28).…”
Section: Prostatementioning
confidence: 99%